Shabik'Eschee Village in Chaco Canyon: Beyond the Archetype. Issue 2 (20th April 2012) - Wills, W. H.; Scott Worman, F.; Dorshow, Wetherbee; Richards-Rissetto, Heather
Abstract: This study revisits an earlier publication in this journal (Wills and Windes 1989) in which a settlement model involving seasonal mobility and limited household autonomy was outlined for Shabik'eschee Village, a Basketmaker III period (ca. A.D. 400–750) site in Chaco Canyon, New Mexico. We return to that work for three reasons. First, the original interpretation has been challenged and an alternative view offered in the form of a large sedentary village. Second, the issue of Basketmaker III sedentism is central to recent efforts to identify and understand a Neolithic Demographic Transition in the northern Southwest. And third, we have obtained new field data from Shabik'eschee and Chaco that contributes to this debate. We conclude that our understanding of Shabik' eschee's history is improved by both new data and the ongoing consideration of alternative models, but the site does not contain evidence for a sedentary village.